2016
DOI: 10.3390/w8120572
|View full text |Cite
|
Sign up to set email alerts
|

Water Balance and Level Change of Lake Babati, Tanzania: Sensitivity to Hydroclimatic Forcings

Abstract: Abstract:We develop and present a novel integrated water balance model that accounts for lake water-groundwater interactions, and apply it to the semi-closed freshwater Lake Babati system, Northern Tanzania, East Africa. The model was calibrated and used to evaluate the lake level sensitivity to changes in key hydro-climatic variables such as temperature, precipitation, humidity and cloudiness. The lake response to the Coupled Model Intercomparison Project, Phase 5 (CMIP5) output on possible future climate out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, according to Cook and Bakker (2012), protection from the risk associated with flood and drought is generally considered a key determinant of water security from an agricultural perspective. However, only the study on Lake Babati, conducted by Mbanguka et al (2016), was found to address the water and climate models together.…”
Section: Resultsmentioning
confidence: 99%
“…However, according to Cook and Bakker (2012), protection from the risk associated with flood and drought is generally considered a key determinant of water security from an agricultural perspective. However, only the study on Lake Babati, conducted by Mbanguka et al (2016), was found to address the water and climate models together.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies we reviewed focused on a water budget from a past research site, perhaps mentioning at the importance of climate change (e.g., Hughes et al., 2022), but did not incorporate bias‐corrected regional climate projections into the data‐driven water budgets. One study that was screened by our search criteria evaluated the sensitivity of the Lake Babati system in East Africa to changes in key hydro‐climatic variables using the Coupled Model Intercomparison Project, Phase 5 (CMIP5) output to understand future risks in water security and flooding (Mbanguka et al., 2016). Dynamic water budget accounting should integrate bias‐corrected regional climate projects to account for the fundamental processes of climate impact on water balance conditions.…”
Section: Discussion and Future Research Opportunitiesmentioning
confidence: 99%
“…Where A(t) is the surface area of the pool obtained using the relationship between surface area and water storage. Evaporation from the pool (E(t)) was estimated similarly to P(t) with evaporation rates derived using the Penman (1948) method, based on weather station data, as it is a commonly-used method for estimating open water evaporation (Mbanguka et al, 2016;Yihdego and Webb, 2018).…”
Section: Water Balance Analysismentioning
confidence: 99%
“…The water balance approach has been widely used to represent and predict changes in water storage of water bodies (Ali et al, 2015). This approach is based on the law of conservation and has been used to understand water fluxes that influence water body dynamics and simulate the water availability in hydrological systems, such as lakes and wetlands (Gronewold et al, 2020;Mbanguka et al, 2016). The water balance, like other methods, requires data or estimates of each of the hydrological components (evaporation, precipitation, surface water in-and outflows and groundwater in-and outflows).…”
Section: Introductionmentioning
confidence: 99%